ANTISIPASI TERJADINYA PEMANASAN GLOBAL DENGAN DETEKSI DINI SUHU PERMUKAAN AIR MENGGUNAKAN DATA SATELIT - Agnes Sri Mulyani (Jurnal Rekayasa Teknik Sipil dan Lingkungan - CENTECH, 2021)
Remote sensing data has capability to detect Water Surface Temperatures in spatial or temporal analysis. Sea surface water temperature (SST) is one of the important indicators of dynamic global climate and dynamic regional climate. The increasing of SST will be effect to global warming and climate change and resulting in disaster such as hurricane, extreme heavy rain, landslide, tornado, melting ice in polar that resulting sea water rises. Indonesia as an Archipelago that consist of ten thousand islands, sea water rise scan cause a small island to sink. This research is aim to early detect SST with Remote Sensing to anticipate Global Warming. The method is literature study from related science journal as a result from researchers. Result of scientist’s researchers in Indonesia show that there has been increase of water surface temperature that has been varied in period over 32 years.It is need an effort to anticipate that there is no disaster. Keywords: Satellite Data;Global Warming;Remote Sensing;Surface Water Temperature